APLIKASI PEMANTAUAN DAN PENGELOLAAN STOCK OPNAME BERBASIS WEB MOBILE DI PERCETAKAN SQUAD COMPUTER - Syahrudin, Syahrudin; Sudewi, Sudewi (JMBI (Journal of Marketing and Business Intelligence), 2025)
In today's technological era, the use of information systems is essential for companies to support managerial decision-making and operational activities, including stock opname (inventory checking). This study focuses on Digital Printing Squad Computer, a company operating in the digital printing sector. The main problem identified is the manual inventory management process, where records of incoming and outgoing goods are still handled without digital systems. This often leads to discrepancies between bookkeeping records and actual stock conditions. The objective of this research is to design and implement a mobile-based information system to enhance the efficiency of stock opname management. The development methodology used is the System Development Life Cycle (SDLC), which is a systematic process for engineering and developing software systems. Data collection methods include literature review, interviews, and direct observation at the company site. The research findings indicate that the implementation of the mobile-based monitoring and inventory management system significantly improves the ease of tracking stock movements at Squad Computer. The system allows real-time recording of goods entering and leaving the inventory, thereby increasing the accuracy and efficiency of stock control operations. Consequently, the developed system not only ensures better data reliability but also supports the company’s management in making more informed and timely decisions.